Pellino3 ubiquitinates RIP2 and mediates NOD2-induced signaling and protective effects in colitis - MCNAMARA, DEIRDRE; FALLON, PADRAIC (My University, 2013)
Mutations that result in loss of function of Nod2, an intracellular receptor for bacterial peptidoglycan, are associated with Crohn's disease. Here we found that the E3 ubiquitin ligase Pellino3 was an important mediator in the Nod2 signaling pathway. Pellino3-deficient mice had less induction of cytokines after engagement of Nod2 and had exacerbated disease in various experimental models of colitis. Furthermore, expression of Pellino3 was lower in the colons of patients with Crohn's disease. Pellino3 directly bound to the kinase RIP2 and catalyzed its ubiquitination. Loss of Pellino3 led to attenuation of Nod2-induced ubiquitination of RIP2 and less activation of the transcription factor NF-κB and mitogen-activated protein kinases (MAPKs). Our findings identify RIP2 as a substrate for Pellino3 and Pellino3 as an important mediator in the Nod2 pathway and regulator of intestinal inflammation.
PUBLISHED
Keywords: Crohn’s disease; Immunology, Inflammation & Infection; Biomedical sciences